Dinamika Komunikasi Antarbudaya Mahasiswa Suku Non Jawa Di Universitas Muhammadiyah Magelang - Sihabuddin Sihabuddin (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2019)
The background of this research is to find out how non-Javanese students at the University of Muhammadiyah Magelang overcame the obstacles of intercultural communication that had been experienced during college. The purpose of this research is to describe and analyze perceptions, adaptation processes, and how to establish intercultural communication relationships non-Javanese students. While the research method uses qualitative methods with a case study approach. The results showed that the non-Javanese students at first considered the language of Javanese as a complicated, foreign language, even ridiculous. However, over time non-Javanese students assessed the Javanese communication as unique, polite, refined in a slow and more careful and multilevel tone. The process of adaptation starts from the awareness of the importance of adapting, followed by learning, and finally learning by practicing. In developing a thigh intercultural communication relations, it prioritizes positive thinking, observing the language and nature of Javanese people first so that they can adjust their style of communication with the Javanese without leaving the identity that they are not Javanese and increase the intensity of intercultural communication.